Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar Siswa Kelas X SMA Negeri 1 Pangsid Sidrap (Studi Pada Materi Pokok Reaksi Redoks) - Nursyam Nursyam; Sumiati Side; Muhammad Jasri Djangi (ChemEdu, 2022)
This research is quasy experiment that aimed to find the effect of cooperative learning model jigsaw type of student’s achievement in class X SMAN 1 Pangsid Sidrap.The study design used is Pretest-Posttest Control Group Design. The sampling technique is done by random sampling so that elected two classes namely class X1 as an experimental class with the number of students 43 and X2 class as control class with the number of students 41 people. Experimental class taught by using cooperative learning model Jigsaw type while the control class was taught by using conventional learning models. The instrument used is result test of learning then it converted into N-Gain. The data was obtained by the N-gain for the experimental class is 0.73 which more high compared with the control class which only by 0.62. Achievement test were analyzed using t-test right parties. T-test results obtained tcalculate = 4,038> ttable = 1.670 in α ═ 0.05. It Concluded that there is a positive effect of cooperative learning model jigsaw type of student’s achievement in class X SMAN 1 Pangsid Sidrap on Redox Reactions subject matter.